Pharmaceutical Applications of Pectin (2021)
Pectin, a natural ionic polysaccharide found in the cell wall of terrestrial plants undergoes chain–chain association to form hydrogels upon addition of divalent cations. Based on its degree of esterification, pectin has been classified into two main types. The high methoxyl pectin with a degree of esterification greater than 50%, which is mainly used for its thickening and gelling properties and the low methoxyl pectin, which is widely used for its low sugar-content in jams, both applications being in the food industry. Pectin is mostly derived from citrus fruit peels, but can also be found in other plants such as waterleaf leaves, cocoa husk, and potato pulps. Pectin has been used as an excipient in pharmaceutical formulations for various functions. This chapter will focus on the various applications to which pectin has been used in the pharmaceutical industry.